Tinjauan Yuridis Terhadap Proses Penerbitan Akta Kelahiran Anak Luar Kawin (Studi Dinas Kependudukan dan Catatan Sipil Kabupaten Batu Bara) - Banun, Sri; Azmi, Muhammad (Media Hukum Indonesia (MHI), 2024)
Children who are state assets who will continue the nation's ideals, it is only right that we as adults and have a healthy mind fight for their rights so that they can grow and develop properly so that there is no more discrimination against the position of illegitimate children who are human beings with inherent dignity and dignity from the womb to death as stated in Law No. 39 of 1999 concerning Human Rights, with a study entitled "Legal Review of the Process of Issuing Birth Certificates for Extramarital Children (Study of the Population and Civil Registration Service of Batu Bara Regency)" aims to analyze the synchronicity and harmony between theory and reality in the field. By using the nature and type of empirical research and qualitative descriptive with the type of data taken and used in this study are primary data and secondary data taken using approach and interview techniques as well as data from archiving and important documents at the Population and Civil Registration Service. The focus of this research conducted in this thesis is on the position of illegitimate children, the role and procedure or process of issuing birth certificates for illegitimate children, starting from the requirements, process and to the final stage, namely the receipt of birth certificates or submission of birth certificates from officers to applicants as well as obstacles and inhibiting factors in the process of issuing birth certificates for illegitimate children. With the data analysis technique used, namely qualitative data analysis, it can be seen that the conditions that occur are less synchronized between theory and what happens in the process of issuing birth certificates for illegitimate children.